Peripheral neuropathies associated with DNA repair disorders. Issue 2 (3rd October 2022) - Maguina, Melissa; Kang, Peter B.; Tsai, Ang‐Chen; Pacak, Christina A.
Abstract: Repair of genomic DNA is a fundamental housekeeping process that quietly maintains the health of our genomes. The consequences of a genetic defect affecting a component of this delicate mechanism are quite harmful, characterized by a cascade of premature aging that injures a variety of organs, including the nervous system. One part of the nervous system that is impaired in certain DNA repair disorders is the peripheral nerve. Chronic motor, sensory, and sensorimotor polyneuropathies have all been observed in affected individuals, with specific physiologies associated with different categories of DNA repair disorders. Cockayne syndrome has classically been linked to demyelinating polyneuropathies, whereas xeroderma pigmentosum has long been associated with axonal polyneuropathies. Three additional recessive DNA repair disorders are associated with neuropathies, including trichothiodystrophy, Werner syndrome, and ataxia‐telangiectasia. Although plausible biological explanations exist for why the peripheral nerves are specifically vulnerable to impairments of DNA repair, specific mechanisms such as oxidative stress remain largely unexplored in this context, and bear further study. It is also unclear why different DNA repair disorders manifest with different types of neuropathy, and why neuropathy is not universally present in those diseases. Longitudinal physiological monitoring of these neuropathies with serial electrodiagnostic studies may provide valuable noninvasive outcome data in the context of future natural history studies, and thus the responses of these neuropathies may become sentinel outcome measures for future clinical trials of treatments currently in development such as adeno‐associated virus gene replacement therapies.